IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN PRAKTIK PEMELIHARAAN SASIS DAN PEMINDAH TENAGA KENDARAAN RINGAN DI SMK MUHAMMADIYAH 1 BANTUL - Yunanto Hanif Hidayah (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study aims to find out: (1) the implementation of 2013 curriculum in PSPTKR practice planning at Muhammadiyah 1 Bantul Vocational School, (2) the implementation of 2013 curriculum in learning activity of PSPTKR practice at Muhammadiyah 1 Bantul Vocational School, (3) and the 2013 curriculum implementation in learning assessment of PSPTKR practice at Muhammadiyah 1 Bantul Vocational School. This study involved 5 PSPTKR subject teachers and all TKR XI grade students as research subjects. Data taken by questionnaires and interviews. Conclusions obtained from the results of two methods and interpreted according to the indicator criteria. The results showed that the implementation of the 2013 Curriculum on aspects of learning planning was included in the fully implemented category with a percentage of 86.35%. However, there are still weaknesess in the implementation of the 2013 curriculum because teachers have not been maximal in applying the RPP principles. In the aspect of learning implementation, the implementation of the 2013 curriculum was included in the fully implemented category with a percentage of 86.92%, but there were still weaknesses in teacher interactions that were less supportive of student activity and active participation. In the aspect of learning assessment, the implementation of the 2013 Curriculum was included in the fully implemented category with a percentage of 81.43%. However, there are still weaknesses in implementing learning assessment because the teacher has not been maximal in using a variety of assessment methods.